2019
DOI: 10.1111/mms.12660
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the vertebral centra in dolphins from the southwestern South Atlantic: A 3D morphometric approach and functional implications

Abstract: In dolphins, centrum shape is one of the features that allows determination of stable and flexible regions in the vertebral column. The Commerson's (Cephalorhynchus commersonii; n = 37), Peale's (Lagenorhynchus australis; n = 24), dusky (Lagenorhynchus obscurus; n = 29), and hourglass dolphins (Lagenorhynchus cruciger; n = 10) are closely related species inhabiting the Southern Hemisphere that have diverse prey and habitat preferences. We applied 3D geometric morphometrics to describe differences in centrum sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
0
7
1
Order By: Relevance
“…sima). In contrast, Marchesi et al (2020a) found morphological differences related to potential differences in thorax flexibility in the four species studied here. This finding was also supported here, as the thoracic region showed heterogeneity in vertebral morphology, allowing to identify two potentially stable areas (Th and ThTa).…”
Section: Morphological Differences and Factors Affecting Swimmingcontrasting
confidence: 87%
See 2 more Smart Citations
“…sima). In contrast, Marchesi et al (2020a) found morphological differences related to potential differences in thorax flexibility in the four species studied here. This finding was also supported here, as the thoracic region showed heterogeneity in vertebral morphology, allowing to identify two potentially stable areas (Th and ThTa).…”
Section: Morphological Differences and Factors Affecting Swimmingcontrasting
confidence: 87%
“…This projection was positioned so that its center would coincide with the anatomical landmark on the center of the centrum face. Accordingly, the vertical line of the "asterisk" passed through the vertical axis of the neural spine (see also Marchesi et al, 2020a). After positioning the projection, we placed one landmark in the center of the face and landmarks on the centrum outline at the intersection of the equiangular radial arrangement and the centrum face outline.…”
Section: D Geometric Morphometricsmentioning
confidence: 99%
See 1 more Smart Citation
“…Caudally, the vertebra with a neural process perpendicular to the body axis after which neural process have caudal orientation was chosen to represent the synclinal point (SP; sensu Slijper, 1936). This vertebra was equivalent to the boundary between mid-and posterior torso employed in previous studies on dolphins (Marchesi et al, 2021;Marchesi, Boy, et al, 2020;. Finally, the central vertebra of the tailstock (TS) was chosen (Figure 2).…”
Section: Samples and Vertebrae Selectionmentioning
confidence: 99%
“…These authors discussed four possible mechanical scenarios that could affect vertebral column regions: areas of potential elastic stability, with short centrum length and low convexity of the faces; areas of potential rigidity, with long centra and low convexity of the faces; areas with high rotation potential but low vertical displacement, with short centrum length and highly convex faces; and areas with high rotation potential and vertical displacement potential, with long centrum length and highly convex faces (see Buchholtz & Schur, 2004;Marchesi, Boy, et al, 2020). Particular vertebral morphologies with adaptive biomechanical implications have been reported for coastal and pelagic cetaceans (see, Buchholtz & Schur, 2004;Gillet et al, 2019;Marchesi, Boy, et al, 2020;Woodward, 2006).…”
Section: Introductionmentioning
confidence: 99%